Analisis Customer Experience terhadap Customer satisfaction pada Aplikasi Spotify melalui Perceived Ease of Use sebagai Variabel Mediasi (Survei Pengguna Spotify Free pada Gen-Z di Kota Sukabumi) - Syahla Nazmi Salsabila; Tetty Sufianty Zafar; Kokom Komariah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid growth of digital music streaming services has intensified competition among platforms, requiring providers to deliver superior user experiences and ease of use to maintain customer satisfaction. Despite its popularity, Spotify Free users, particularly from Generation Z, still encounter various limitations that may affect their overall satisfaction. This study aims to examine the effect of customer experience on customer satisfaction with perceived ease of use as a mediating variable among Spotify Free users from Generation Z in Sukabumi City. This research employed a quantitative approach using a causal associative design. Data were collected through an online questionnaire distributed to 195 respondents selected using purposive sampling. The measurement instrument was developed based on established indicators of customer experience, perceived ease of use, and customer satisfaction. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3.2.9 software. The findings indicate that customer experience has a positive and significant effect on customer satisfaction and perceived ease of use. Furthermore, perceived ease of use significantly influences customer satisfaction and acts as a mediating variable in the relationship between customer experience and customer satisfaction. These results suggest that enhancing user satisfaction can be achieved not only through positive experiential factors but also by improving the perceived simplicity and usability of digital applications.